Engineerable mesenchymal stem cell-derived extracellular vesicles as promising therapeutic strategies for pulmonary fibrosis - Yixiang Chen; Moxuan Li; Juntao Yang; Yuqi Chen; Jiancheng Wang (Stem Cell Research & Therapy)
Abstract Pulmonary fibrosis (PF) is a progressive and fatal interstitial lung disease characterized by fibroblast activation, excessive extracellular matrix deposition, and irreversible lung damage. Current therapeutic interventions, including anti-fibrotic medications and lung transplantation, are constrained by limited efficacy, adverse side effects, and logistical challenges. Mesenchymal stem cell-derived extracellular vesicles (MSC-EVs) have emerged as a promising cell-free therapeutic approach due to their safety, scalability, and capacity to deliver bioactive cargo. These nano-sized vesicles replicate the regenerative and immunomodulatory properties of their parent cells, targeting dysregulated signaling pathways and pathological cellular phenotypes associated with PF. MSC-EVs modulate fibrosis by restoring alveolar epithelial cell function, suppressing myofibroblast activation, and regulating immune responses, such as macrophage polarization and neutrophil infiltration. However, challenges such as limited clinical efficacy and insufficient targeting hinder the broad application of MSC-EVs. Engineering strategies like preconditioning, drug loading, and surface modification can solve the above issues. Our review synthesizes PubMed/Google Scholar literature up to Feb. 2025 on MSC-EVs’ targeted PF therapy and engineering strategies, aiming to translate preclinical insights into clinical use.